Blow-up of Solutions to Reaction-diffusion System with Nonstandard Growth Conditions - Gurusamy, Arumugam; Balachandran, Krishnan (Journal of Applied Nonlinear Dynamics, 2026)
This paper is concerned with the existence and blow-up of solutions of reaction diffusion system with p(x)− growth conditions. The existence of weak solution is proved by using the Galerkin method. The blow-up of solutions is established by applying the method of comparison with suitable blow-up of self-similar subsolutions. Finally the theoretical results are illustrated by numerical examples.